THE ROLE OF ARTIFICIAL LIGHTING IN INCREASING THE SPIRITUALITY OF WORSHIP SPACES (STUDY GKJ MERGANGSAN, YOGYAKARTA) - Nimas Sekarlangit; Frengky Benediktus Ola (MODUL, 2025)
Worship spaces support spiritual practices and foster religious community, where lighting influences the atmosphere and worship experience. Many traditional churches, including the Mergangsan GKJ, tend to prioritise the basic function of illumination without maximising its spiritual potential, resulting in suboptimal conditions that diminish devotion. Ideally, artificial lighting design should be comprehensive, integrating function with psychological and spiritual dimensions. The warm natural lighting mimics natural afternoon light and is believed to create a calm, comfortable atmosphere and enhance spiritual connection. Simulation using Dialux is an effective tool for optimising this design. This study aims to analyse the role of artificial lighting in the Mergangsan GKJ in creating a spiritual atmosphere. The methodology used is a mixed approach: quantitative simulation using Dialux Evo to analyse existing lighting conditions and alternative warm natural lighting scenarios, and a qualitative literature review of lighting standards and the spiritual function of light. The results indicate that the Mergangsan GKJ artificial lighting meets functional illumination standards in all main areas (altar, music/gamelan room, lower and upper congregation areas). The choice of colour temperature 3000K (Warm White) and CRI 80 consistently creates a warm and comfortable atmosphere that supports solemnity, proving a new contribution in integrating functionality and spirituality in architectural lighting design.